اللسانيات التطبيقية الحديثة للمتخصصين في العربية وآدابها: مدخل وصفي = Al-Lisaniyat al-tatbiqiyah al-hadithah - Ali, Asem Shehadeh Saleh; Dollah, Nafi@Hanafi; Haji Ibrahim, Majdi; Ismail, Yasir (IIUM Press, 2015)
-